- KEWENANGAN GUBERNUR DKI JAKARTA DALAM MENETAPKAN HARGA ECERAN TERTINGGI GAS BERSUBSIDI MENURUT PERATURAN GUBERNUR : - - Raja Arviary Rezky Haryono; Reni Dwi Purnomowati (Faculty of Law, Universitas Trisakti, 2023)
Determination of Highest Retail Price LPG is important matter to highlight because it’s important for many people. HET in DKI Jakarta is based on the current Governor's Regulation that was made because the mandate from Minister of Energy and Mineral Resources regarding the Provision and Distribution of LPG. But in 2021 this Candy has changed and becomes a juridical problem for the validity and existence of Governor Regulation issued in 2015. This study is a normative juridical research that will be analyzed qualitatively. The conclusions chosen from a deductive logic point of view. The authority of the Governor of DKI Jakarta in Setting the HET for subsidized Gas in terms of laws and regulations from the Minister of Energy and Mineral Resources Number 28 of 2021 concerning Amendments to Minister of Energy and Mineral Resources Number 26 of 2009. Local governments are given authority to make regulations that shows the role of governor in deconcentration. implementation of Governor Regulation Number 4 of 2015 is running well and effectively. It’s hoped that consistency of local government to become a supervisor in implementing regulations regarding the HET for LPG gas is expected so there are no parties selling LPG gas above HET price